The increasing incidence and high body mass index-related burden of gallbladder and biliary diseases–A results from global burden of disease study 2019 - Liu, Shuhua; Yi, Maolin; Qin, Juanjuan; Lei, Fang; Lin, Lijin; Li, Yi; Zhuo, Ming; Liu, Weifang; Huang, Xuewei; Cai, Jingjing; Zhang, Xiaojing; Zhang, Peng; et al. (Frontiers in Medicine, 2022)
Background: Gallbladder and biliary diseases are common gastrointestinal conditions associated with huge socioeconomic costs and are considered risk factors for cardiovascular diseases and digestive system cancers. The global disability-adjusted life years of gallbladder and biliary diseases were not adequately controlled from 1990 to 2019. Several non-communicable diseases were associated with the incidence of gallbladder and biliary diseases. It is necessary to clarify the change in the incidence and disability burden of gallbladder and biliary diseases worldwide. Methods: Data on high body mass index (BMI)-related disease burden and incidence, years of life lost prematurely, and years lived with disability (YLDs) due to gallbladder and biliary diseases were obtained from the Global Burden of Disease 2019. The estimated annual percentage change was calculated to qualify the gallbladder and biliary disease burden change. Results: The global age-standardized incidence rate has increased from 585.35 per 100 000 (95%UI: 506.05-679.86) in 1990 to 634.32 per 100 000 (95%UI: 540.21-742.93) in 2019. And the increase in incidence was positively correlated with rising high BMI-related summary exposure value. The high BMI-related YLDs of gallbladder and biliary diseases have increased worldwide over time. Globally, the 25-49 age group suffered a rapid rise in incidence and high BMI attributable to the YLD rate of gallbladder and biliary diseases. Conclusions: The global incidence and high BMI-related YLDs of gallbladder and biliary diseases remain prominent to increase over the past 30 years. Notably, the incidence and high BMI-related YLDs among people aged 25-49 years have rapidly increased over time. Therefore, high BMI should be emphasized in strategic priorities for controlling gallbladder and biliary diseases. Keywords: gallbladder and biliary diseases; incidence; high body mass index; years lived with disability; people aged 25-49 years